Case Report and Literature Review of Conjunctival Melanoma in the Black Population - Oscar Chen; Fae Kayarian; Elaine Kelly; Richard J. Grostern; Anjali Tannan (Case Reports in Ophthalmological Medicine)
Conclusions: CM has rarely been observed in the black population. With this current case report, there are only 47 black patients found in the literature with this ocular surface tumor. Further detailed documentation on the presentation, location, and outcomes of CM in this population is imperative to better screen and treat this demographic.